An evaluation of ELISA using recombinant Brucella abortus bacterioferritin (Bfr) for bovine brucellosis. (April 2016) - Hop, Huynh Tan; Arayan, Lauren Togonon; Simborio, Hannah Leah; Reyes, Alisha Wehdnesday Bernardo; Min, WonGi; Lee, Hu Jang; Lee, Jin Ju; Chang, Hong Hee; Kim, Suk
Highlights: The cloning and expression of Brucella abortus bacterioferritin (Bfr) was accomplished by an expression vector system, and purification of a recombinant B. abortus Bfr (rBfr). The immunogenicity of rBfr was confirmed by Western blot with Brucella -positive serum. rBfr-based ELISA was performed, resulting in rBfr being able to detect anti- Brucella antibodies in positive sera with TAT without any immunoreaction with Brucella -negative or Yersinia enterocolitica O:9 sera. Abstract: To date, detection of antibodies against the lipopolysaccharide portion is the backbone of most serodiagnostic methods for brucellosis screening. However this pose a risk for false positive reactions related to other pathogens especially that of Yersinia enterocolitica O:9 which has the most prominent cross reactivity with Brucella spp. In this study, cloning and expression of Brucella abortus bacterioferritin (Bfr) was accomplished by PCR amplification into an expression vector system, and purification of a recombinant B. abortus Bfr (rBfr). The immunogenicity of rBfr was confirmed by Western blot with Brucella -positive bovine serum. To determine whether rBfr has a potential benefit for use in the serodiagnosis of bovine brucellosis, rBfr-based ELISA was performed. Interestingly, rBfr was able to detect anti- Brucella antibodies in positive sera in a dependent manner of TAT values but did not show an immunoreaction with negative samples. Particularly, average OD492 values at the lowest, medium and highest TAT titer levels were 1.4, 2.2 and 2.6-fold increase compared with the cutoff value, respectively. The accuracy, specificity and sensitivity of rBfr showed 89.09%, 93.6% and 85.33%, respectively. These findings suggest that rBfr might be a good candidate for serological diagnosis development of bovine brucellosis.